2018
DOI: 10.3989/mc.2018.11316
|View full text |Cite
|
Sign up to set email alerts
|

A composite cement of high magnesium sulphate resistance

Abstract: This study investigates the magnesium sulphate resistance of chemically activated phosphorus slag-based composite cement (CAPSCC). Enough mortar specimens were prepared from phosphorus slag (80 wt.%), type II Portland cement (14 wt.%), and compound chemical activator (6 wt.%) and were exposed to 5% magnesium sulphate solution after being cured. Mortar specimens of both type II and V Portland cements (PC2 and PC5) were also prepared and used for comparison purpose. According to the test results, after 12 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…From the detailed experimental investigation on loss in compressive strength of both type of concrete specimens exposed to Sulphate salt solution (2.0g/l) up to 360 days, it was found that as exposure period increases loss in strength is also increases because of with time C-S-H gel production decreases which is mainly responsible for strength and subsequent leaching of Portlandite. These ndings are in concurrence with the observation of some authors (Boudali et al 2016, Allahverdia et al 2018). In the hydration of cement at initial stage some Ettringite is also formed but these are unstable and with reaction of remaining Tricalcium aluminate it forms Mono sulphoaluminate, Its crystals are stable in Sulphate de cient solution but in the presence of excessive Sulphate ions in the environment, these crystals revert back in the Ettringite which is responsible for deterioration in long term.…”
Section: Hardened Propertiessupporting
confidence: 93%
See 1 more Smart Citation
“…From the detailed experimental investigation on loss in compressive strength of both type of concrete specimens exposed to Sulphate salt solution (2.0g/l) up to 360 days, it was found that as exposure period increases loss in strength is also increases because of with time C-S-H gel production decreases which is mainly responsible for strength and subsequent leaching of Portlandite. These ndings are in concurrence with the observation of some authors (Boudali et al 2016, Allahverdia et al 2018). In the hydration of cement at initial stage some Ettringite is also formed but these are unstable and with reaction of remaining Tricalcium aluminate it forms Mono sulphoaluminate, Its crystals are stable in Sulphate de cient solution but in the presence of excessive Sulphate ions in the environment, these crystals revert back in the Ettringite which is responsible for deterioration in long term.…”
Section: Hardened Propertiessupporting
confidence: 93%
“…The combined acid-sulphate attack caused by Ammonium sulphate is characterized by decomposition/ softening, expansion, cracking, and spalling. Allahverdia et al 2018, investigated the effect of Magnesium sulphate on a chemically activated phosphorus slag-based composite cement concrete and found that the compressive strength of specimens increased initially during the rst few months of exposure. The limited increase in compressive strength is attributed primarily to the progress of hydration reactions within the specimen and, to a lesser extent, to the deposition of Gypsum in regions close to the exposed surfaces, resulting in densi cation; however, continued exposure resulted in continuous compressive strength reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The compressive strength increased for the control mixes, mix1 with (OPC+PW) and mix3 with (SRPC+PW) by 21.8%, 23% at 180 days respectively. While it decreased for mix2 with (OPC+WW) and mix4 with (SRPC+WW) by 25%, 12.5% at 180 days respectively, the reason behind that was the use of well water, which has a negative effect on the compressive strength of concrete when it is compared to potable water [8][9][10][11][12][13][14][15][16][17][18][19][20]. Water impurities that conflict with the setting of cement influence concrete durability and strength negatively.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Consequently, it causes cracking in concrete, which increases permeability, paving the way for aggressive water to penetrate the concrete. The ability of concrete to resist sulfate attack is affected by the cementitious composition of concrete and the permeability of concrete [10]. Moreover, cement type and water/cement ratio have a substantial effect on the resistance and durability of the concrete [11].…”
Section: Introductionmentioning
confidence: 99%
“…Seawater is a complex solution, and soluble salt ions can corrode the cement soil in seawater such as Cl − , SO 2− 4 , and Mg 2+ [1]. Extensive research indicates that corrosive ions change the composition and structure of cement soil, reduce its strength, and increase its permeability, affecting the service life of related projects [2][3][4][5][6][7]. ere are plenty of studies on the reduction in the strength of cement soil caused by seawater corrosion.…”
Section: Introductionmentioning
confidence: 99%